SOCIAL PROGRAMMING AS A MECHANISM FOR SOCIAL SECURITY - Xidirov Suxrob Norbo‘tayevich (Bright Mind Publishing, 2025)
This article explores the concept of social programming as a key mechanism for ensuring social security in modern societies. It highlights how targeted state programs, policies, and interventions reduce poverty, inequality, and social risks while promoting social stability. The paper analyzes existing literature on welfare systems and social policy, presents methodological approaches for studying social programming, and evaluates its outcomes in terms of security, resilience, and sustainable development. The findings suggest that social programming not only addresses immediate needs but also contributes to long-term social cohesion and economic stability.
Keywords: Social programming, social security, welfare policy, poverty reduction, inequality, social stability, public policy.